Are Sequential Round-Robin Tournaments Discriminatory? - Marco Sahm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
I examine sequential round-robin tournaments with three and four symmetric players which are matched once with each other. If the matches are organized as Tullock contests (all-pay auctions), the tournament is almost fair (highly discriminatory): Subject to the position of their matches in the sequence of the tournament, the differences in players' ex ante winning probabilities and expected payoffs are small (large). Discrepancy results from a higher discriminating power of the all-pay auction.
Keywords: C72; D72; Z20; 330